Crop diversification strategies for minor irrigation schemes: Proceedings of the workshop organized by the Irrigation Research Management Unit, Irrigation Department and the Sri Lanka National Program, International Irrigation Management Institute, held at the Irrigation Department, Colombo, Sri Lanka on 20 February 1996 - Marambe, B.; Sangakkara, U.R.; Haq, K.A. (Irrigation Department of Sri Lanka, 1996)
The last few decades Sri Lanka has made detennined efforts for crop diversification to raise farm production and improve the quality of life of the farmers. Significant progress has also been made and a large area has been brought under different crops, especially, chili and big onion, two very important cash crops. Most of these developments have occurred in medium and major schemes resulting in significant increases in the cropping intensity as well as in the participation of farmers. Minor schemes which command around 42 percent of the total irrigated area of the country, however did not benefit much from the crop diversification program and their cropping intensity to fluctuate between 80 percent and 90 percent for nearly half a century. At the same time, because of increasingly reduced return from rice farming, many farmers in these schemes are looking for off farm employment to make a living. To understand the technical and socioeconomic dynamics and develop strategies for crop diversification in minor schemes, the Irrigation Research Management Unit (IRMU) of the Irrigation Department (ID) in collaboration with the Sri Lanka National Program (SLNP) of the International Irrigation Management Institute (IIMI) organized a consultation workshop on strategies for Crop diversification in Minor Irrigation Schemes. This volume is the report of the proceedings of the above workshop held at the Irrigation Department, Colombo, Sri Lanka on 20 February, 1996. The workshop provided an opportunity to the participants from different organizations to exchange experiences and identify new approaches to crop diversification.